What Keck and Mithouard Should Have Said: Same Same, but Different - Elisabeth Schöyen (European Papers, 2023)
(Series Information) European Papers - A Journal on Law and Integration, 2023 8(1), 373-383 | What Should Have Said | (Abstract) This rewriting of Keck and Mithouard aims to retain the ‘spirit’ of Keck without resorting to categorising national measures into ‘product requirements’ and ‘certain selling arrangements’. The judgment is informed by Senn and Nussbaum’s capability approach and a social justice perspective on the free movement of goods. To this effect, Schøyen’s judgment affirms that only national measures which either negatively impact the competitive position of goods from other Member States or prevent their market access altogether require justification. Thus, the judgment clarifies that product requirements in the sense of Cassis de Dijon are measures having equivalent effect because they impose a double burden on foreign producers. The Sunday trading case law, by contrast, is overturned, like in Keck itself.